Structure and organisation of 47 nutrition support teams in Germany: a prospective investigation in 2000 German hospitals in 1999 - Shang, Edward; Suchner, U.; Dormann, A.; Senkal, Metin (European journal of clinical nutrition, 2003)
Objective: Evaluation. Contrary to the Anglo-American region, very little is known in Germany on the structure and organisation of nutrition support teams (NST).